Pengaruh Media Pembelajaran Uno Stacko Mathematic (USMAT) Terhadap Hasil Belajar Matematika Siswa - Saba Pasinggi, Yonathan; Lukman; Dalle, Asriah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This research aims to determine the effect of the Uno Stacko Mathematic (USMAT) learning media on the mathematics learning outcomes of class III students at UPT SD Negeri 3 Macorawalie, Sidrap Regency. The approach used is a quantitative approach with experimental research type and Pre Experimental design in the form of One Group Pretest-Posttest Design. The type of sampling technique used is purposive sampling technique. Data analysis uses descriptive statistical analysis techniques and inferential statistical analysis techniques. The results of descriptive statistical analysis showed that the student's initial test score (pretest) was 47.14 and increased after being given treatment (posttest) to 82.38. The results of inferential statistical analysis by testing the hypothesis using the paired sample T-test show a significance of 0.001<0.05, this shows that H0 is rejected and H1 is accepted. Based on these results, it can be concluded that the Uno Stacko Mathematic (USMAT) learning media influences the mathematics learning outcomes of class III students at UPT SD Negeri 3 Macorawalie, Sidrap Regency.